Adaptación de los productores a los riesgos que amenazan la economía de la producción de maíz duro en el Cantón Mocache para reducir su impacto en el bienestar familiar. - Guadamu Montes, Betsy Elizabeth (2019)
In the present research work entitled "Adaptation of producers to risks that threaten the economy hard corn production in the canton Mocache to reduce its impact on household welfare". In which the general objective was to study mechanisms of adaptation of the producers was held against perceived threats to the economy hard corn production in the canton Mocache. The methodology used was a field research with the implementation of the survey technique where qualitative and quantitative information was obtained. The results indicate that the risks that small and medium producers are exposed in each crop cycle are increased pest weeds and diseases 100% climate variation 95%, low selling prices 75%, lack of financing 62% increased production costs 46%, among others, with the risks of climate and increased pests and diseases that most perceive producers. Practices used by producers to address threats that arise in each crop cycle are: chemical to control disease in growing 100%, reduce cost of labor 78%, water 60%, pay growing 49% negotiate the sale of the crop at an affordable price 40%, to acquire funding from family or friends 33%, crop rotation 23%. There are several risks that arise in this economic activity that producers in this area are losing attractiveness to continue producing corn, orienting the production of other crops to ensure their family economy. Keywords: corn, risks, adaptation, adaptive practices